Travel Wild Wisconsin : A Seasonal Guide to Wildlife Encounters in Natural Places - Andrews, Candice Gaukel (Book collections on Project MUSE., 2013)
Have you ever heard a wolf howl in Wisconsin's Northwoods, watched thousands of ancient sturgeon roil the waters of one of the largest inland lakes in the United States, or tagged a monarch butterfly before it begins one of the world's great migrations to its winter habitat in Mexico? This book is a seasonal guide to genuine wildlife encounters with an array of birds, mammals, fish, and insects in Wisconsin's most beautiful natural settings: state wildlife areas, rivers, lakes, flowages, and preserves, as well as in national wildlife refuges and forests.